FINANCIAL CONTROL OF UNIVERSITIES - Tatiana A. Pankratova (Статистика и экономика)
The task of ﬁnancial control is in the showdown deviations from accepted standardsand violations of the principles of legality, efﬁciency, effectiveness and efﬁciencyof resource management. Availability of ﬁnancial control in the public institution(university) is a prerequisite for efﬁcient operation in the field of education forthe purpose of preventing, detecting andcombating ﬁ nancial crimes.